2023
DOI: 10.1088/1758-5090/ace0db
|View full text |Cite
|
Sign up to set email alerts
|

Gelatin methacryloyl and Laponite bioink for 3D bioprinted organotypic tumor modeling

Abstract: Three-dimensional (3D) in vitro tumor models that can capture the pathophysiology of human tumors are essential for cancer biology and drug development. However, simulating the tumor microenvironment is still challenging because it consists of a heterogeneous mixture of various cellular components and biological factors. In this regard, current extracellular matrix (ECM)-mimicking hydrogels used in tumor tissue engineering lack physical interactions that can keep biological factors released by encapsulated cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…GelMA has proven to have good transport of nutrients and oxygen that enables cell response over time. (30,31) A recent model showed the encapsulation of human pancreatic cells and stromal fibroblasts in GelMA (8% w/v) with the photoinitiator LAP could mimic cell-ECM interactions and is proven to have a good diffusion of nutrients and oxygen, which allowed the cells to proliferate in the GelMA beads. (32) Using the GelMA hydrogel, we were able to increase the thickness of our first model and still have a higher number of live cells compared to dead cells.…”
Section: Discussionmentioning
confidence: 99%
“…GelMA has proven to have good transport of nutrients and oxygen that enables cell response over time. (30,31) A recent model showed the encapsulation of human pancreatic cells and stromal fibroblasts in GelMA (8% w/v) with the photoinitiator LAP could mimic cell-ECM interactions and is proven to have a good diffusion of nutrients and oxygen, which allowed the cells to proliferate in the GelMA beads. (32) Using the GelMA hydrogel, we were able to increase the thickness of our first model and still have a higher number of live cells compared to dead cells.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, during the degradation study, this sample absorbs a greater quantity of water containing collagenase enzyme, leading to the highest degradation rate observed among the samples studied. Conversely, the 5G1.5L and 5G2L samples, featuring smaller pore sizes and lower swelling ratios, demonstrate reduced rates of degradation as shown in Figure S2 [69]. This property renders them well-suited for more prolonged in vitro investigations, such as on-chip applications.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, to improve the printability and shape fidelity of pure GEL, it has been used with other natural and synthetic polymers and successful results have been reported for instance methacrylated GEL [11,12], oxidized alginate (ADA)-GEL [13], GELsilk [14] and GEL-chitosan [15]. In numerous studies, methacrylated GEL has been used due to the easy cross-linkable property using UV light [16]. In another study, Negrini et al demonstrated a GEL biomaterial ink with a different crosslinking approach, N,N ′ -methylene bisacrylamide (MBA) was used as a crosslinker and included in the GEL solution before 3D printing and the hydrogels were printed on a cooled surface [17].…”
Section: Introductionmentioning
confidence: 99%